1988
DOI: 10.1093/ajcp/89.4.488
|View full text |Cite
|
Sign up to set email alerts
|

DRC Antigen Expression in B-Cell Lymphomas

Abstract: DRC (dendritic reticulum cell) antigen expression was studied in 38 cases of B-cell lymphomas including follicular lymphoma. The results of this study showed DRC-1 to be expressed in 1/3 of small lymphocytic; 3/3 of mantle zone lymphoma (MZL); 10/10 of follicular, small cleaved; 6/7 of follicular, mixed; 1/2 of follicular, large cell lymphomas. However, DRC-1 was not expressed in any of diffuse, small cleaved (0/6) and diffuse, large cell (0/6). Although S-100 protein was positive in the majority of these DRC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
6

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
1
15
0
6
Order By: Relevance
“…The CD5+/DRC -I+/slgD-+/LN2 + findings in our patient imply that this is MCL [6,8,13,14,15]. The ALP+/cyclin DI-findings and the lymphoepithelial lesions with bile ducts in the patient imply that this is a marginal zone B-cell lymphoma [10,11].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The CD5+/DRC -I+/slgD-+/LN2 + findings in our patient imply that this is MCL [6,8,13,14,15]. The ALP+/cyclin DI-findings and the lymphoepithelial lesions with bile ducts in the patient imply that this is a marginal zone B-cell lymphoma [10,11].…”
Section: Discussionsupporting
confidence: 47%
“…MCL is characterized by the t (11;14) translocation and its molecular counterpart bcl-1 rearrangement, which may result in an overexpression of the PRAD-1/cyclin D1 gene [3,4,21] and cyclin DI protein expression [17,23]. Extranodal MCL has been reported [8,14,15,16,19]. However, to our knowledge hepatic MCL has not been reported previously.…”
Section: Introductionmentioning
confidence: 97%
“…The relationship noticed between the tumour mass of low grade B-cell lymphomas and the number and size of the follicular dendritic cell clusters, favours the view that follicular dendritic cells progressively develop as the neoplastic process spreads 25 . Together with the results observed in high grade B-cell lymphoma and in reactive bone marrows, it could support the hypothesis that the presence of follicular dendritic cells in bone marrow lymphoid infiltrates is not strictly linked to a malignant process, but possibly to a long-lasting chronic proliferation or reaction, as opposed to an acute proliferation or a transitory reaction.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, DRC-1 was not expressed in the other three types of lym phomas, except in 1 case of SL (case 14). We performed DRC staining with S-100 protein on the paraffin sections [20] of this particular case of SL and found that DRC-1 was positive in pseudofollicular proliferation centers. There fore, of the four lymphoma types, we consider DRC-1 pos itivity to be a characteristic of MZL.…”
Section: Discussionmentioning
confidence: 95%